(untitled) (Journal of Interdisciplinary Insights, 2024)
This study examines customer perceptions and satisfaction at the Khuslen Wholesale Center, a key retail hub in Darkhan-Uul aimag, amidst the growing emphasis on customer satisfaction across all sectors. Recognizing the critical importance of improving service quality, accessibility, and effectiveness in the trade sector, a comprehensive customer satisfaction survey was conducted using the internationally validated SERVQUAL model, which encompasses five dimensions and 22 measures developed by Parasuraman, Zeithaml, and Berry. The research involved surveying 760 customers through a structured questionnaire to assess the current state of customer satisfaction. Findings reveal strengths in the center’s internal environment and staff professionalism, while highlighting areas for improvement in the external environment and service efficiency. Customers expressed a need for better accessibility and a wider range of services, indicating opportunities for enhancing overall satisfaction and loyalty. The study suggests that strategic enhancements, such as improving infrastructure, elevating product presentation, expanding service offerings, and investing in digital marketing, could significantly boost customer satisfaction and support the sustainable growth of the Khuslen Wholesale Center.